Maslahat ve siyaset görüşleri bağlamında Karâfî’nin tazir anlayışı - Uyar, Muhammed Erkam (My University, 2018)
İslam ceza hukukunda tazir cezaları siyasi otoritenin yetkisine havale edilmekle birlikte taziren cezalandırmalarda üst sınırın ne olacağı hususu tartışmalıdır. İlk dönemlerde ağırlıklı görüş tazirin üst sınırının had cezaları olduğu belirtilirken sonraları taziren katlin cevazı tartışılır olmuştur. Bu tartışmada taziren ölüm cezası verilebileceği görüşleri daha çok Türklerin İslam dünyasına hâkimiyetleri sonrasına tekabül etmektedir. Karâfî, Türklerin İslam dünyasına hakim olduğu dönemlerde yaşamış Maliki bir fakih olarak bu tartışmada taziren katli tereddütsüz savunanlar arasındadır. Mürsel maslahatlarla amel etmenin herhangi bir şartı olamayacağını savunan müellifin siyasi otoriteyle alakalı görüşleri toplum menfaati bağlamında incelendiğinde onun tazirle alakalı görüşlerinin maslahat ve siyaset düşüncesiyle irtibatlı olduğu ortaya çıkmaktadır. Bu çalışmada, onun maslahat ve siyaset görüşleri temeline dayanan tazir anlayışının mahiyeti ve sonrakilere etkisi ele alınmıştır.

Although there is a general agreement that the political authortity is authorized in tazir penalties in Islamic law, the issue of what the upper limit in these penalties is a debatable point. In earlier periods of Islam, the upper limit of tazir penalties was stated by a majority up to the had penalties, but later the mentioned expression has become discussable as a death penalty. And there is a relationship between the thought in which the upper limit of the tazir could be considered as a death penalty and the sovereignty of Turk-Mongol states over the Muslim lands. As a Mâlîkî Faqih who lived in the Mameluke Egypt in that period, Karâfî, is one of the first defenders of who they argue that the death penalty is legitimate as a tazir, precisely. Because of his thoughts about public interest and politic, he is certain that there should not be any limitation in tazir penalties. He rejects what Gazzâlî has stated the in frame of the necessity of three prerequisits about acceptance of mürsel maslaha (necessity, certanity and generality). According to Karâfî, as long as one, especially the political authortity, treats the community considering the public interest, he has a legitimate power, if not more so. İn this study, his tazir opinions on which based his thoughts about public interest and the politic are examined and some of his effects on Ottomans tried to be shown.
Keywords: Ceza (İslam hukuku); Islamic law; İslam hukuku; Maslahat Tazir; Policy; Public Interest; Punishment (Islamic law); Siyaset; Tazir